Religious Tolerance, Education and the Curriculum
XIII, 148 p.
Keywords: The creation of a secular education system was one of the great social experiments designed to break down religious intolerance within society. One element of this design was administrative, involving the creation of non-denominational schools, and another element involved a centralised curriculum. In this collection of essays, political philosophers, lawyers, sociologists, theologians and educators explore the role of state schools in promoting tolerance within 21st century multicultural, religiously pluralistic societies. How may different models of liberalism in the secular state have different outcomes in relation to religious tolerance in the education system? Does a state education system have a role in teaching values such as tolerance, and if so, how is this best achieved? How are epistemology and truth connected with tolerance? How does the ideal of a ‘value free’ secular education mask the values that the secular state teaches? The essays are written from both theoretical and practical perspectives and engage with each other directly to address one of the significant issues of our day. This is the fourth volume arising from a series of conferences on the theme of ‘Negotiating the Sacred’. Previous volumes have included /Blasphemy and Sacrilege in a Multicultural Society; Blasphemy and Sacrilege in the Arts; and Medicine, Religion and the Body.